Census report on Chinese urological surgeons - Yinghao Sun; Liqun Zhou; Junhua Zhang; Nianzeng Xing; Qian Zhang; Xiuzhong Hu; Linhui Wang; Yinglu Guo (Asian Journal of Urology)
Objective: To grasp the general situation of Chinese urological surgeons and the status quo of their scientific research, work and training, thus providing valuable recommendations for urological talent team construction in future. Methods: The survey respondents were the urological surgeons, who held the Certificate of Medical Practitioner in the People's Republic of China, whose scope of practice was confined to urological surgery. The urological surgeons involved in the project completed an online questionnaire survey. All the data were collected through the internet. Results: There were a total of 18 981 urological surgeons in China in 2015, of whom 15 875 from 2 602 hospitals participated in this project, with a mean age of 39.64 years old. In 2015, 1 949 631 cases of surgery were performed, including 493 723 cases of open surgery, 1 146 444 cases of endoscopic/laparoscopic surgery (robot-assisted laparoscopic surgery were excluded), 6 259 robot-assisted surgery and other types of urological surgery. Besides, Chinese urological surgeons published 1 358 monographs as well as 14 558 academic papers, and also obtained 2 064 scientific funds in 2015. A total of 92 122 person-time participated in academic conferences. Urological surgeons with higher educational degrees as well as higher academic titles and from Eastern China or higher-level hospitals had more opportunities to participate in further education and training. Conclusion: This is the very first census conducted through internet on urological surgeons' multiple aspects. After analyzing and summarizing the data collected, the Census could improve the quality of urological diseases diagnosis and treatment in China. Keywords: Census, Surgeons, Hospitals, Surgery, Education, Laparoscopy, Endoscopy